Preparation and permeability study of polysulfone membrane for CO2 separation - Ida Nuryani, Ibrahim (2008)
Polysulfone membrane is one of the potential candidates to be used as membranes for gas separation. With a nonporous and dense membrane structure, the membrane can be applied in a wide range of temperature and pressure. Polysulfone membrane was prepared by mixing a dope, where polysulfone (PSU) polymer was mixed with N, N-Dimetilacetamide (DMAc). Permeability of the membrane was examined by using the gas permeability unit available in the Gas Lab. Four membrane samples have been produce with different characteristics which were membrane A, membrane B, membrane C and membrane D namely. Membrane A is straight away immersed in water for ten second, membrane B was exposed in air and has an immersion time of 1 minute, membrane C was straightly immersed in water for one day while membrane D was exposed to air for one minute and immersed in water for a day. Measured permeability data in polysulfone (glassy polymer) was consistent with literature studies. In this regard, immersion time of membrane gave impact in membrane performance. This behavior was found from CO2 permeability value for membrane A was the lowest and the membrane D gave the highest permeability value. It showed that the permeability of membrane D was the best compared to the other 3 membranes with the permeability of membrane A, B, C and D was 0.0824, 0.0827, 0.0837 and 0.1015 cm/s.bar respectively. From the data and supported theories by various authors, it can be concluded that different immersion time gave impacts to the performance of polysulfone polymer membrane for CO2 separation.